The Role of Government and Trust in the Market Economy - Nadja König; Ludger Schuknecht (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper studies the role of governments and its link to trust. We argue that the public's trust strongly depends on governments delivering on their core tasks in a market economy. In some economies, a neglect of core tasks can be observed and there seems to be some erosion, notably in terms of securing sound rules of the game in industrialised countries. We find very little correlation between government expenditure and trust but a strong correlation with delivering on core tasks. This leads us to conclude that it is not government spending per se that needs to increase to build trust, but rather better focused government activities.
Keywords: H11; H41; H50; 330; role of government; public goods; trust in government; quality of public finances